PENGARUH PENERAPAN METODE INTERVENSI SEMANTIK DIVERGEN TERHADAP AFASIA TRANSKORTIKAL MOTORIS: Effect of Application of Divergent Semantic Interventional Therapy Method on Motor Transcortical Aphasia - Santi Komaladini; Popon Popon (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2021)
This study aims to determine the application of the divergent semantic intervention method in motor transcortical aphasia clients after stroke, male gender aged 44 years at the Cibabat Regional General Hospital. The research method used is a case study research experiment which aims to determine the condition of the subject before and after intervention through therapy. Data collection was carried out through the WOTS stage, namely (1) interviews with the client's parents, (2) direct observation of the client, (3) conducting tests on the client, and (4) studying the patient's medical record document. The results of the research after doing therapy using the divergent semantic intervention method for 15 meetings obtained good results by assessing the level of words on nouns. The conclusion is that the divergent semantic intervention method has an effect on mentioning the level of objects